Digital Picture Books for Young Dual Language Learners: Effects of Reading in the Second Language - Tunkiel, Katarzyna A.; Bus, Adriana G. (Frontiers in Education, 2022)
Reading picture books in the first language (L1) before rereading them in the second language (L2) is assumed to be beneficial for young dual language learners (DLLs). This pilot study examined how sharing digital picture books in L1 or L2 at home before reading them in L2 in kindergarten affected L2 book-specific vocabulary learning and story comprehension. Participants were 14 three- and four-year-old children who spoke Polish at home and learned Norwegian as their second language. Even when DLLs were less advanced in L2, reading first in L1 was not advantageous for L2 vocabulary learning. Characteristics of caregiver–child interactions during the reading of digital picture books in L2 may explain why home reading in L2 was more beneficial than reading in L1 for less proficient young L2 learners.